Activated protein C protects against renal ischaemia/reperfusion injury, independent of its anticoagulant properties - Lattenist, Lionel; Jansen, Marcel P. B.; Teske, Gwendoline; Claessen, Nike; Meijers, Joost C. M.; Rezaie, Alireza R.; Esmon, Charles T.; Florquin, Sandrine; Roelofs, Joris J. T. H. (Thrombosis and Haemostasis, 2016)
Acute renal failure, a serious condition characterised by a drastic decline in renal function, often follows ischaemia/reperfusion (I/R) episodes. I/R is characterised by necrosis, inflammation and activation of coagulation, in concert causing renal tissue damage. In this context, activated protein C (APC) might be of importance in the pathogenesis of renal I/R. APC is a serine protease which has anticoagulant but also several anti-inflammatory and cytoprotective effects such as protection of endothelial barrier function. It was our objective to study the role of cytoprotective and anticoagulant functions of APC during renal I/R. C57BL/6j mice subjected to renal I/R were treated with intraperitoneally injected exogenous human APC, or two mutant forms of APC(200 µg/kg) which specifically lack anticoagulant or signalling properties. In a different experiment mice received specific monoclonal antibodies (20 mg/kg) that block the cytoprotective and/or anticoagulant properties of endogenous APC. Treatment with APC reduced tubular injury and enhanced renal function without altering the inflammatory response and did reduce renal fibrin deposition. Administration of APC mutant lacking anticoagulant properties reduced renal damage and enhanced renal function. Blocking the anticoagulant and cytoprotective functions of endogenous APC resulted in elevated tubular damage and reduced tubular cell proliferation, however, without influencing renal function or the inflammatory response. Furthermore, blocking both the anticoagulant and cytoprotective effects of APC resulted in dramatic renal interstitial haemorrhage, indicative of impaired vascular integrity. Blocking only the anticoagulant function of APC did not result in interstitial bleeding. In conclusion, the renoprotective effect of APC during I/R is independent of its anticoagulant properties.
Keywords: Acute Kidney Injury; haemostasis; ischaemia-reperfusion injury; kidney; protein C